LGBTQI rights are human rights: A Namibian perspective (Journal for Studies in Humanities and Social Sciences, 2020)
The Namibian Constitution has been noted to be modern, progressive and internationally exemplary but fails to include and recognise the rights of the Lesbian, Gay, Bisexual, Transgender, Queer and Intersex (LGBTQI) community. Chapter III of the Namibian Constitution, which is based on the Universal Declaration of Human Rights, focuses on “Fundamental Human Rights and Freedoms” and these rights were the “very principles Namibians had fought for” (Geingob, 2004, p.135). During the apartheid regime, many Namibians were not privileged to enjoy these basic human rights since oppression and discrimination against “different” people was the order of the day. Even though the fight for political independence is over, the fight for equality and inclusivity still continues. This paper explores the Fundamental Human Rights and Freedoms in the Namibian Constitution; extracting key information from other legal instruments to highlight the inherent contradictions in the protection of certain rights. It specifically focuses on the right to be free from discrimination of any kind and the right to assembly and association (marriage). This paper recommends that sodomy be decriminalised, same-sex marriages and joint adoption (same sex) be legalised in Namibia sincethe criminalisation and illegality of these add to extreme intolerance of differences, discrimination, exclusion and societal divide.
Keywords: LGBTQI; same-sex marriages; same-sex adoption; discrimination; sodomy; immoral practices